(untitled) (Eurasian Scientific Herald, 2022)
In any country of the world, there is a practice in the production of hydrocarbons that plays a huge role - the structures of geological exploration. Uzbekistan is not an exception to the rule here. In our country, great efforts are being made to explore new deposits of hydrocarbon raw materials. In the current conditions, when the wealth of the country’s subsoil is a source of prosperity and economic growth of the country, the activities of UZBEKGEOPHYSICS JSC can be considered very important in this area